Evaluation of fiberglass derived three dimensional geomaterial for problematic soil applications - Mujah, Donovan; Hazarika, H.; Ahmad, F.; Rahman, Ekhlasur (GEOMATE International Society, 2013)
This research was aimed to study the potential reuse of recycled glass fiber-derived three dimensional geomaterial obtained from industrial glass fiber wastes to innovate a sustainable, cost-effective geosynthetic for ground improvement in problematic soil application. The ready availability, high tensile strength, lightweight and non-biodegradable characteristics of glass fibers further elevate their advantages as compared to the presently adopted geosynthetics in soft soil reinforcement condition. In this study, mechanical properties of rectangular strip shape, ‘8’ shape and bolted screw ‘8’ shape samples and pullout resistance force of glass fibers geomaterials were investigated by considering glass fibers’ layer thickness, shape formation and orientation in a laboratory scale model. It was observed that the tensile and yield strengths of overall geomaterial samples significantly increase as strip layers thickness increase. Results from both the tensile strength and pullout resistance force indicated similar trend of increasing in strength values with test conducted using other type of geosynthetics in various soil media to simulate the action of different soil conditions at real sites.